(untitled) (Research, Society and Development, 2022)
Food supplements are conceptualized with substances added to the diet, with the aim of complementing, supplying nutritional deficiencies or even to improve physical performance. Whey protein is the popular term for a dietary supplement based on whey protein. The aim of this study was to review the main consequences associated with dietary supplementation with whey protein. The methodology consists of an integrative literature review, being an exploratory bibliographic research with a qualitative and descriptive approach. The initial sample contained 130 articles, which were submitted to the inclusion and exclusion criteria, at the end 6 articles were selected to compose the discussion. Through the reviewed studies, it was possible to conclude that nutritional supplementation with whey protein brings benefits, helping to maintain lean mass, increase body strength and especially in post-exercise muscle recovery. However, the big problem is the indiscriminate consumption and without professional guidance, excessive supplementation with whey protein can cause liver and kidney damage, compromising the health of the individual. In this context, it is important to consult a qualified professional to carry out the indication of the product and the appropriate amount for each individual.